From the ancient Silk Road to the belt and road initiative: narratives, signalling and trust-building - Zhao, Yujia; Tan-Mullins, May (2021)
Narratives help in interpreting and understanding surrounding political realities. Yet, the divergence of narratives may also create distrust, and it is an important reason for greatly diverging perceptions of the Belt and Road Initiative (BRI) between China and the international community. This paper explores how trust can be bridged between different narratives. It discusses the notions of trust and how the Chinese concept of ‘brightness’ contributes to a strategic signalling process for trust-building in strategic cooperation. This paper proposes that trust-building is a process of signalling and knowledge building. Only when the signal sent for strategic cooperation fits the other parties’ knowledge about the sender, can the trust-building process succeed. This compatibility between signals and developed knowledge can be the result of several rounds of signalling, in which the signal sender’s honesty regarding their self-interests and intentions is the necessary pre-condition.